Smoke and mirrors : globalized terrorism and the illusion of multilateral security - Harvey, Frank P. (University of Toronto Press, 2004)
"In Smoke and Mirrors, Frank P. Harvey mounts a powerful case for American unilateralism by exposing the real costs, potential risks, and catastrophic failures of multilateral alternatives that are rarely acknowledged by proponents. He addresses the relationship between globalization, terrorism, and unilateralism, and provides a systematic explanation for, and defence of, Washington's response to threats of terrorism and proliferation of weapons of mass destruction." "Smoke and Mirrors will compel critics of the Bush administration to move beyond the assumption that American foreign policies are temporary in nature. Indeed, the tensions caused by terrorism and proliferation will continue to shape Washington's threat perceptions and responses for decades. The book challenges critics to demonstrate the successes - as distinct from the promises - of multilateral security and to prove that their preferred alternative has achieved the victories that would justify a sweeping rejection of unilateralism."--Jacket